Study on the Thermoelectric Properties of NdZnSbO - Liu, Jian (International Journal of Materials Science and Technology Studies, 2024)
The thermoelectric properties of NdZnSbO have been systematically studied using density functional theory calculations. The bulk NdZnSbO is a natural super lattice structure with low thermal conductivity and low electrical conductivity. The band structure indicates that it is a direct gap semiconductor with a band gap of 0.68eV. Its conductivity can be improved by doping and thus increase its ZT value. At a temperature of 800K, near the carrier concentration 2.1E19/cm3, the p-type doped system presents a Seeback coefficient of 382μVκ-1, a conductivity of 1.48×104Sm-1 and a power factor of 0.66×10-3Wm-1κ-2. As a result, a thermoelectric figure of merit (ZT) reaches a maximum value of 1.12.